ISLAMIC EDUCATION AND MILLENNIAL CHARACTER CHALLENGES: THE URGENCY OF INSTILLING SHIDDIQ, AMANAH, TABLIGH, AND FATHONAH VALUES IN SCHOOLS - Zainuri, Ach. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze and understand the process of internalizing the values of  Islamic teachings  in  forming students with  Siddiq, Amanah, Tablig, and Fatonah characters. This research is a qualitative descriptive case study type research.  The  case  study  in  this  research  is  in-depth  research  about  an individual, a group, an organization, an activity program, and so on at a specific time.  This  type  of  descriptive  research  aims  to  explore  and  describe  social reality, describing many variables related to the problem and unit being studied. This research was conducted at the institution at MA Miftahul Ulum Pakuniran Probolinggo.  The  data  analysis  technique  in  this  research  uses  the  Miles  and Huberman data analysis model with stages of data reduction, data display, and conclusion. The results of the research conducted show that the application of internalizing  the  values  of  Islamic  teachings  forms  students  with  Siddiq, Amanah,  Tablig,  and  Fatonah  characters,  including  (1)  Transformation  of Islamic teaching values in forming students with the four characteristics of the prophet at MA Miftahul Ulum Pakuniran. The transformation stage is carried out by distributing material by PAI teachers. (2) Transaction of Islamic teaching values in forming students with the four characteristics of the prophet at MA Miftahul  Ulum  Pakuniran.  In  the  transaction  stage,  the  teacher  discusses  the material  with  students  in  the  classroom.  (3)  Transinternalization  of  Islamic teaching values in forming students with the four characteristics of the prophet at  MA  Miftahul  Ulum  Pakuniran.  The  teacher's  transinternalization  stage provides examples, familiarizes with, implements, and forms student character student activities in daily life in the school environment.